Rafael Cadenas receiving the Premio Cervantes :: "It is necessary, in countries where it (democracy) exists, a pedagogy that strengthens it". (Mayéutica Revista Científica de Humanidades y Artes, 2023)
Speech by Venezuelan poet Rafael Cadenas, upon receiving the Premio Cervantes 2022. Ceremony held on April 24, 2023 in Alcalá de Henares.